Correlations between Physical Activity and Social Health, Moral Development and Physical Fitness among Middle School Students - Hassan Shafaei; Niloofar Rezaei; Sadie Mohammadi; Saeed Ghorbani (Shiraz University of Medical Sciences, 2024)
Background: Sports and physical activity (PA) are recognized not only as beneficial activities but also as complex phenomena with a variety of functions. The present study aimed to examine the association between children's PA and their social health, moral development, and physical fitness.Methods: This was a descriptive-correlational study. The study included 384 middle school students who were selected through convenience sampling method (average age of 14.12 years) from Tehran, Iran, in 2023. We used Physical Activity Questionnaire for Adolescents, Keyes's Social Well-being Questionnaire and Moral Development Questionnaire for measuring PA, social health and moral development, respectively. Physical fitness was measured using two tests including "Shuttle Run 4*9" and "Stork Balance Stand". The data were analyzed using both the independent t-test and Pearson correlation test.Results: There were no gender differences among boys and girls regarding age and BMI (both P>0.05). Children had a medium level of PA (2.65 out of 5); PA showed direct and significant correlations with social health (r=0.539, P<0.001), moral development (r=0.427, P<0.001) and physical fitness (r=0.630 and r=0.408, both P<0.001). Moreover, boys had significantly higher PA (P<0.001), social health (P<0.001), moral development (P<0.001), and physical fitness (P<0.001) than girls.Conclusions: These results suggested the necessity to enhance the level of physical activity (PA) among middle school students. Furthermore, it is advised that physical education teachers and sports coaches incorporate physical education programs to promote PA in middle school students.